Strategi Pondok Pesantren Modren IGM Al Ihsaniyah Palembang Dalam Membangun Ekosistem Kewirausahaan - juliana, Riksi; Aliasan, Aliasan; Muslimin, Muslimin (CV. ITTC INDONESIA, 2022)
IGM Al Ihsaniyah Palembang Modern Islamic Boarding School Strategy in building an entrepreneurial ecosystem. This study seeks to uncover the entrepreneurial strategy used by the Islamic Boarding School IGM Al Ihsaniyah Palembang, this research uses field research, with primary data sources and secondary data sources, while data analysis in this study uses observation, interviews, and documentation. The data analysis technique in this study is descriptive qualitative, for the purpose of this research is the entrepreneurial strategy at the IGM Al Ihsaniyah Palembang Islamic Boarding School and the inhibiting factors for entrepreneurship at the IGM Al Ihsaniyah Islamic Boarding School Palembang. The results of this study are that the entrepreneurial strategy used by the IGM Al Ihsaniyah Islamic Boarding School, Palembang, is divided into 4, namely the disciplinary approach strategy, socialization strategy, cooperative strategy, and marketing strategy which are 5P namely price, product, promotion, place, resources man. While there are 5 obstacles to entrepreneurship, namely lack of discipline, guardian of students, lack of time sharing, human resources, and money control.